The potential of tasmannia lanceolata as a natural preservative and medicinal agent: antimicrobial activity and toxicity - Winnett, V.; Boyer, H.; Sirdaarta, J.; Cock, I. E. (Pharmacognosy Communications)
Introduction: Tasmannia lanceolata is an endemic Australian plant with a history of use by indigenous Australians as a food and as a medicinal agent. Methods: T. lanceolata solvent extracts were investigated by disc diffusion assay against a panel of bacteria and fungi and their MIC values were determined to quantify and compare their efficacies. Toxicity was determined using the Artemia franciscana nauplii bioassay. Results: All T. lanceolata extracts displayed antibacterial activity in the disc diffusion assay. The berry methanolic extract had the broadest antibacterial range, inhibiting the growth of all 18 of the bacteria tested (100%). The berry water and ethyl acetate, extracts were also good antibacterial agents inhibited the growth of 17 (94.4%) and 15 (83.3%) of the 18 bacteria tested respectively. Strong inhibitory activity was detected with MIC values as low as 4.8 μg/ml against some bacteria, although many of the measured MIC’s were several orders of magnitude higher than this. All extracts were equally effective at inhibiting the growth of both Gram-negative bacteria and Gram-positive bacteria. In contrast, only the T. lanceolata peppercorn extracts were effective as antifungal agents (albeit with limited antifungal ranges), inhibiting the growth of 2 of the 4 fungal species tested each (50%). All T. lanceolata extracts were non-toxic in the Artemia fransiscana bioassay with LC50 values greatly in excess of 1000 μg/ml. Conclusions: The lack of toxicity of the T. lanceolata extracts and their potent broad spectrum inhibitory bioactivity against bacteria and fungi indicates their potential as natural food preservatives and as medicinal agents in the treatment and prevention of microbial diseases.
Keywords: Winteraceae; Tasmannia lanceolata; Tasmanian pepper; Australian plants; antibacterial; medicinal plants; food spoilage; food poisoning